Dynamics of Learning Autonomy in Economics Learning: A Bibliometric Exploration - Sadiah, Emas; Purnamasari, Imas (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to map the development of learning autonomy research in economic learning through bibliometric analysis of Scopus-indexed publications for 2005–2025. The method used is bibliometric, with the stages of identification, selection, and document analysis using the Biblioshiny R application. From 17,104 initial publications, 30 selected relevant documents were analyzed in depth. The novelty of this study lies in the systematic mapping of trends, collaboration patterns, and thematic dynamics of learning autonomy research that has not previously been explored quantitatively in economics. The main findings show an annual publication growth of 5.65%, with dominant contributions from authors and institutions in China, especially Hunan University and author Chen L. The primary focus of the research remains on the issues of "autonomous learning", "learning autonomy", and "learner autonomy". However, integrating new topics, such as artificial intelligence, blended learning, and soft skills development, has begun to stand out since 2018. International collaboration has begun to develop, but its intensity is still low, and contributions from other countries are still limited. The main recommendation is to increase international and multidisciplinary collaboration and expand contributions from institutions and countries outside China. Future research is suggested to further integrate digital technologies and soft skills in the context of learning autonomy.